Acceptance and Perception toward Using Digital Technology in the Classroom among Students and Teachers in Ogun State, Nigeria - T. O. Abiodun; A. Asanre; A. Awofala (Journal of Science Education Research, 2023)
Digital technology has been recognized as a powerful tool in teaching and learning Mathematics. Proper usage of digital technology would enhance students’ and teachers’ effectiveness in the classroom setting. This study investigated the acceptance and perception of using digital technology in the classroom among students and teachers in reference to Ogun in Nigeria. The study used a survey-type descriptive research design. Three hundred and sixty (360) respondents consisting of three hundred (300) students and sixty (60) teachers made up the sample for this study. In the investigation, a Multi-stage Sampling Technique was adopted. In the first stage, the researchers selected ten (10) secondary schools in Ogun State with digital technology facilities using the Purposive Sampling Technique. In the second stage, the researchers selected six (6) teachers and thirty (30) pupils from each of the selected schools using the Simple Randomly Sampling Technique. The instrument for data collection was titled “Acceptance and Perception on Digital Technology Questionnaire”. (APDTQ) Using Cronbach's alpha, the instrument's reliability was assessed, and a reliability coefficient of 0.82 was calculated. The content validity was ascertained by the preparation of the table of specifications. Four research questions were answered. Data collected were analyzed using the descriptive statistics of mean, standard deviation, and percentages. Results of the findings showed that both teachers and students had favorable opinions on the usage of digital technology in the classroom, although students were shown to be more perceptive than teachers. Additionally, the study's findings indicated that both teachers and students highly embrace the use of digital technology in the teaching and learning of mathematics. It was recommended, among others, that additional knowledge about using digital technology in the classroom should be given to teachers and students.